Infestation. Svea Bräunert’s glance through the prism of the RAF-spectre (KULT_online, 2016)
Which role does the RAF play for Germans’ self-image? To what extent does left-wing terrorism play part of their cultural history since 1945? How does art mirror this role, becoming a “prism” to make memory’s traumatic structure visible? Svea Bräunert’s attempt to discuss all of these questions as intrinsically connected, leads into a complex analysis of the – especially in Germany – multifaceted relation between present, past, and future. Images distributed by mass media become as much a factor in this approach as does their appropriation and modification through specific artworks. Against this background the RAF no longer appears as a phenomenon of the 1970s and ’80s, but as a spectre of German postwar history up to the present.